REFERENCE VALUES OF AORTIC PULSE WAVE VELOCITY IN A LARGE HEALTHY POPULATION AGED BETWEEN 3 AND18 YEARS - Erzsebet Valeria Hidvegi; M. Illyes; B. Benczur; Renata M. Bocskei; L. Ratgeber; Z. Lenkey; Ferenc T. Molnar; A. Cziraki (Педиатрическая фармакология, 2013)
Objective: The measurement of aortic pulse wave velocity (PWVao) is an accepted marker in stratifying individual cardiovascular risk in adults. There is an increasing volume of evidence concerning impaired vascular function in different diseases in paediatric populations, but, unfortunately, only a few studies are available on the measurement of normal PWVao values in children. The aim of our study was to determine the reference values of PWVao in a large healthy population using a newly developed technique. Methods: Three thousand, three hundred and seventyfour healthy individuals (1802 boys) aged 3–18 years were examined by an invasively validated, occlusive, oscillometric device. Results: The mean PWVao values increased from 5.5_0.3 to 6.5_0.3 m/s (P<0.05) in boys and from 5.6_0.3 to 6.4_0.3 m/s (P<0.05) in girls. The increase, however, was not constant, and the values exhibited a flat period between the ages of 3 and 8 years in both sexes. The first pronounced increase occurred at the age of 12.1 years in boys and 10.4 years in girls. Moreover, between the ages of 3 and 8 years, the brachial SBP and mean blood pressures increased continuously and gradually, whereas the PWVao remained unchanged. By contrast, beyond the age of 9 years, blood pressure and aortic stiffness trends basically moved together. Conclusion: Our study provides the largest database to date concerning arterial stiffness in healthy children and adolescents between the ages of 3 and 18 years, and the technology adopted proved easy to use in large paediatric populations, even at a very young age.